Factors Associated With Nonattendance for Osteoporosis Evaluation Following Fragility Fracture - Thany Seyok; Jamie E. Collins; Cole Hodys; Samantha J. Erikson; Samantha Perez Menendez; Brandon E. Earp; Julia F. Charles (Journal of Osteoporosis)
Conclusion: Inpatient evaluation and treatment for osteoporosis should be considered in patients who are older or have sustained a hip fracture as they may have more difficulty attending post-fracture appointments.